Using Library Funds to Support Open Access Publishing through Crowdfunding: Going Beyond Article Processing Charges. Issue 2 (3rd April 2018) - Reinsfelder, Thomas L.; Pike, Caitlin A.
ABSTRACT: Publishers commonly use Article Processing Charges (APCs) to fund open access publications, and some libraries and institutions help local authors pay these costs. However, this strategy is expensive and can usually only address one article at a time. A number of relatively new publishing initiatives rely on a crowdfunding model and allow many libraries to share the cost of open access, often at a fraction of the cost of APCs. This article highlights several alternative publishing projects to help librarians think further about how library funds could be used to support open access.